Evaluation of Lactobacillus spp. as a Probiotic Agent against Pathogenic Bacteria - Suhad Faisal Hatem Al-Mugdadi (Journal of Global Pharma Technology, 2017)
Objective: The World Health Organization (WHO) and Agriculture Organization of the United Nations (FAO) defined the robotics in this manner: ‘live microorganisms which, when administered in enough amounts, give a health benefit on the host’. One of the significant features of robotic lactobacilli is to make aggressive activity against pathogenic bacteria because of their ability to produce lactic acid and other organic acids that reduce the pH in the human intestine, in addition to bacteria in and H2O2, which consider a unfriendly environment for the development and survival of various pathogenic bacteria. This study aimed to studying the effect of crude supernatant cell free component extracted from Lactobacillus sp. natural isolate from vagina and commercial sheet including Lactobacillus fermentum, Lactobacillus delbruekii as aprobiotic against various pathogenic bacteria isolates which is multidrug resistance. Materials and Methods: The lactic acid bacteria were isolated from two sources including Lactobacillus sp. from healthy vaginal swabs and commercial Lactobacillus fermentum and Lactobacillus delbruekii as a sachets on MRS selective media agar and broth. Cell free supernatant was extracted from Lactobacillus spp. by using autoclave and cooling centrifuge to evaluate it as Robotic in vitro using agar well diffusion method. Result Anti-bacterial activity of  lactobacillus sp. Isolate supernatant free cells  against pathogenic bacteria by using heat (autoclave) showed biological effect on K. pneumonia(28mm) E.coli in urine(20mm), S .aureus in ear(24mm) , S. aureus in vagina(28mm), Candida albiccans in vagaina (6mm), H. influence in sputum(10mm), K. pneumonia sputum(6mm) and Seriesin wound(16mm).No effect of supernatant was shown by using cooling centrifuge. Commercial mixture of Lactobacillus fermentum, Lactobacillus delbruekii supernatant cell free of these strains which obtained by Cooling centrifuge and Autoclave showed variation in diameter inhibition zones but it still less than  diameter of  zones of vaginal lactobacillus sp. Supernatant. Conclusion: The efficiency of fresh curd supernatant of lactobacilli from healthy vagina in addition to the commercially available lactobacilli strains consider, as a good robotic and therapeutics against pathogenic bacteria. In addition this results conclude that effect components (supernatant) obtained by the heating consider better method than cooling.Keywords: Lactobacillus spp, Probiotic, pathogenic bacteria, Antibacterial activity.